PENGARUH INTERAKSI TEMAN SEBAYA TERHADAP PERILAKU KEAGAMAAN REMAJA DI KORONG BATIAH-BATAIAH, NAGARI GADUR, KECAMATAN ENAM LINGKUNG - Al Fajrani; Sulaiman Sulaiman (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to determine the effect of peer interaction on adolescent religious behavior in Korong Batiah-BatiahNagariGadur, Six Lingkung District. The research method used in this research is quantitative using correlational methods. The population of this study were teenagers who were in Korong Batiah-Batiah, totaling 60 teenagers. Data on peer interaction and religious behavior were obtained from questionnaires, in which the questionnaire met the validity and reliability requirements of the instrument. The data analysis technique in this study uses simple linear regression analysis, which meets the requirements of the classical assumption test (normality and linearity), f-test, t-test, and coefficient of determination. Based on the results of the f-test analysis, it was obtained f count = 20,984 ? f table = 4.00, then the results of the analysis of the coefficient of determination (r2) obtained the value of r2 = 26.6%, which means that the peer interaction variable is influenced by religious behavior variables by 26.6% and the remaining 73.4% is influenced by other factors. So it can be seen that if someone gathers with people who are diligent in worship or pray in congregation, then he will be like that and if he gathers with someone who likes to gamble, then more or less he will be like that too.